The importance of research on enteroparasitosis in the State of Pará (PA), Brazil (Research, Society and Development, 2025)
Research on enteroparasitosis in the state of Pará is extremely important due to the high rates of parasitic infections in this region. Investigating enteroparasitosis is essential to understand the prevalence of infections, associated risk factors and control and prevention strategies. The objective of the study is to analyze the incidence and distribution of enteroparasitosis, identify the main parasites involved, understand transmission patterns and investigate the socioeconomic and environmental factors that contribute to the spread of parasitic infections. The aim is to achieve a better understanding of the epidemiological situation of enteroparasitosis in the state of Pará, providing data for the implementation of effective prevention and control measures. Furthermore, research can contribute to improving public health, improving health policies aimed at combating parasitic infections and promoting the well-being of the population.